2020
DOI: 10.9734/ajopacs/2020/v8i130104
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Fatty Acid Composition of Ocimum basilicum L. Seed Oil

Abstract: Ocimum basilicum has been widely used in traditional medicine. Rural communities have used fixed oils for variety purposes since a long time ago. They used for cosmetic applications, fuel, medicine and food. The aim of this study was to characterize the physicochemical properties and fatty acid composition of O. basilicum seed oil. Lipids were determined by continuous extraction in a Soxhlet apparatus for 6 hours using hexane as solvent. The physicochemical properties of the oil were assessed by standard and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
1
21
2
Order By: Relevance
“…This can be explained by the inversion of LA and ALA in basil seed oil that occurs in certain species [51]. Furthermore, in Table 4, the samples from Iran [47], Canada [51], and Vietnam [30] exhibited higher amounts of ALA, while the Singapore [30], Sudan [42], and United Arab Emirate [52] samples had higher amounts of LA. These differences in the fatty acid compositions can be attributed to environmental and climatic factors; although, according to Mostafavi et al [33] and Choi et al [30], the plant genotype is the most important parameter.…”
Section: Lipidsmentioning
confidence: 96%
See 3 more Smart Citations
“…This can be explained by the inversion of LA and ALA in basil seed oil that occurs in certain species [51]. Furthermore, in Table 4, the samples from Iran [47], Canada [51], and Vietnam [30] exhibited higher amounts of ALA, while the Singapore [30], Sudan [42], and United Arab Emirate [52] samples had higher amounts of LA. These differences in the fatty acid compositions can be attributed to environmental and climatic factors; although, according to Mostafavi et al [33] and Choi et al [30], the plant genotype is the most important parameter.…”
Section: Lipidsmentioning
confidence: 96%
“…Finally, in a recent study by Idris et al [42], the physicochemical characteristics and fatty acid composition of O. basilicum seed oil were reported. It was shown that this oil can be used in countless applications due to the high content of essential fatty acid, such as LA and ALA.…”
Section: Benefits Of Fatty Acids From Basil Seedsmentioning
confidence: 97%
See 2 more Smart Citations
“…Fatty acid methyl esters needed by the industry are linolenate (ω-3), linoleate (ω-6) [5], oleate (ω-9) [6], and stearate [6][7][8]. Stearic acid or stearate is an SFA found in palm oil and sunflower [6,9], Nymphaea pubescens seeds [10], Ocimum basilicum [5], candlenut [11,12], sesame [13], Cactus opuntia dillenii [14], sacha inchi [15] and almond seeds [16]. Nymphaea pubescens seeds contain stearic acid as palm oil and peanut oil [10].…”
Section: Introductionmentioning
confidence: 99%